2012
DOI: 10.1073/pnas.1201816109
|View full text |Cite
|
Sign up to set email alerts
|

Expression reduction in mammalian X chromosome evolution refutes Ohno’s hypothesis of dosage compensation

Abstract: Susumu Ohno proposed in 1967 that, during the origin of mammalian sex chromosomes from a pair of autosomes, per-allele expression levels of X-linked genes were doubled to compensate for the degeneration of their Y homologs. This conjecture forms the foundation of the current evolutionary model of sex chromosome dosage compensation, but has been tested in mammals only indirectly via a comparison of expression levels between X-linked and autosomal genes in the same genome. The test results have been controversia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
179
3
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(197 citation statements)
references
References 38 publications
14
179
3
1
Order By: Relevance
“…We next looked specifically at the evolution of the putative DEC genes preferentially expressed in the breast. Following a previous study 19 , we calculated a breast biased index (BBI) for each of the B700 putative DEC genes by dividing its expression level in the breast by its median expression level in all 16 normal tissues, obtaining 73 genes with BBI42 (Supplementary Data 5). We clustered the expression profiles of these 73 genes based on the pairwise Euclidean distance of these tissues or cells.…”
Section: Resultsmentioning
confidence: 99%
“…We next looked specifically at the evolution of the putative DEC genes preferentially expressed in the breast. Following a previous study 19 , we calculated a breast biased index (BBI) for each of the B700 putative DEC genes by dividing its expression level in the breast by its median expression level in all 16 normal tissues, obtaining 73 genes with BBI42 (Supplementary Data 5). We clustered the expression profiles of these 73 genes based on the pairwise Euclidean distance of these tissues or cells.…”
Section: Resultsmentioning
confidence: 99%
“…If the X chromosome is upregulated, transcriptional output from the present-day X and its autosomal progenitor should be similar. These studies found transcription from the current eutherian (the mammalian clade that includes humans and other placental mammals) X chromosome to be significantly lower compared to its autosomal progenitor (Julien et al 2012;Lin et al 2012). However, X and autosomal progenitor expression levels were similar when analyses were limited to highly expressed genes and those encoding for proteins involved in large (more than seven subunits) complexes (Julien et al 2012;Lin et al 2012).…”
Section: Transcription Increases To Above Autosomal Levels When the Dmentioning
confidence: 90%
“…To test Ohno's hypothesis more directly, attempts have been made to define those genes present on the autosomal progenitor of the X chromosome using species from major mammalian and bird lineages (Julien et al 2012;Lin et al 2012). If the X chromosome is upregulated, transcriptional output from the present-day X and its autosomal progenitor should be similar.…”
mentioning
confidence: 99%
“…This has most likely resulted in a twofold up-regulation of dosage-sensitive X-Chromosomal gene expression in males (Nguyen and Disteche 2006;Deng et al 2011Deng et al , 2013Brockdorff and Turner 2015). In addition, changes in autosomal genes whose products act in conjunction with Xencoded proteins contributed to a re-establishment of balanced gene expression (Julien et al 2012;Lin et al 2012;Necsulea and Kaessmann 2014). It is thought that up-regulation of the dosagesensitive genes on the X forced the specific inactivation of one of the two X Chromosomes in females (X Chromosome inactivation [XCI]) (Lyon 1961).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%